Preparation and evaluation of novel microemulsion-based hydrogels for dermal delivery of benzocaine - Üstündağ Okur, Neslihan; Çağlar, Emre Şefik; Arpa, Muhammet Davut; Karasulu, Hatice Yeşim (Taylor & Francis Ltd, 2017)
The purpose of the current research was to prepare and evaluate the potential use of microemulsion-based hydrogel (MBH) formulations for dermal delivery of benzocaine (BZN). The pseudoternary-phase diagrams were constructed for various microemulsions composed of isopropyl myristate (IPM) as oil phase, Span 20, Tween 20, Tween 80, cremophor EL and cremophor RH40 as surfactants, ethanol as cosurfactant and distilled water as aqueous phase. Finally, concentration of BZN in microemulsions was 2% (w/w). The physicochemical properties, such as conductivity, viscosity, pH, droplet size, polydispersity index and zeta potential of microemulsions, were measured. Carbopol 940 was used to convert BZN-loaded microemulsions into gel form without affecting their structure. Furthermore, excised rat abdominal skin was used to compare permeation and penetration properties of BZN loaded M3 and M3BHs with BZN solution. According to ex vivo study results, BZN-loaded M3BH1 showed highest flux values and high release rate values, and furthermore, this gel formulation had low surfactant content. Finally, in order to learn the localization of formulations within the dermal penetration, formulations and BZN solution were labeled with red oil O and subjected to fluorescence observation. In conclusion, BZN-loaded MBHs could be offered as a promising strategy for dermal drug delivery.
WOS: 000399500700007
PubMed ID: 26738443
Keywords: Benzocaine; Dermal Drug Delivery; Characterization; Fluorescence Observation; Microemulsion; Microemulsion-Based Hydrogel